MAKNA SIMBOL SASTRA LISAN TANDUK MASYARAKAT ADAT GENAHARJO KABUPATEN TUBAN - S, Suantoko (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2017)
Abstract: This research aims to understand the meaning of tanduk oral literary symbol of the indigenous society of Genaharjo, Tuban. Through the semiotic theory of Charles S. Pierce, it can be understood that the tanduk oral literature has the meaning of symbols represented in the meaning of symbols of the names of characters, the meaning of animal symbols, the meaning of food symbols, and the meaning of plants symbols. The meanings that exist in the tanduk oral literature that evolved in the Genaharjo indigenous society formally refer to a single meaning of life that life should give priority to salvation in prayer. Local people believe that true life in the world is salvation. Every tanduk of its formal essence begs for salvation and blessing from God.The idea of ​​salvation is the attitude and outlook of human life towards God, the universe, and fellow human beings. Keywords: symbol of meaning, indigenous society of Genaharjo, tanduk oral literature Abstrak: Penelitian ini betujuan untuk memahami makna simbol sastra lisan tanduk masyarakat adat Genaharjo Kabupaten Tuban. Melalui teori semiotik Charles S. Pierce, dapat dipahami bahwa sastra lisan tanduk memiliki makna simbol yang direpresentasikan pada makna simbol nama tokoh, makna simbol binatang, makna simbol makanan, dan makna simbol tumbuh-tumbuhan. Makna-makna yang ada dalam sastra lisan tanduk yang berkembang dalam masyarakat adat Genaharjo secara formal mengacu pada satu makna hidup bahwa kehidupan harus mengutamakan keselamatan dalam berdoa. Masyarakat setempat meyakini bahwa hidup sejati di dunia adalah keselamatan. Setiap tanduk esensi formalnya memohon keselamatan dan keberkahan dari Tuhan. Paham keselamatan yang dimaksud adalah sikap dan pandangan hidup manusia terhadap Tuhan, alam semesta, dan sesama manusia. Kata Kunci: makna simbol, masyarakat adat Genaharjo, dan sastra lisan tandukPermalink/DOI: http://dx.doi.org/10.15408/dialektika.v4i1.6999